Look into my eyes - Child, Lauren (Child, Lauren. Ruby Redfort (Series), 2018)
Thirteen-year-old Ruby, a genius code-cracker and daring detective, gets an anonymous call setting a challenge that leads her to the headquarters of Spectrum, a highly secret anti-crime agency that needs her help to crack a code, but soon Ruby uncovers dastardly plans of the Fool's Gold Gang.